Total ankle replacement in patients with von Willebrand disease: mid-term results of 18 procedures - Barg, Katharina; Schneider, Stefan W. (Haemophilia, 2015)
von Willebrand disease (VWD) is a recognized cause of secondary ankle osteoarthritis (OA). Few studies have examined orthopaedic complications and outcomes in VWD patients treated for end-stage ankle OA with total ankle replacement (TAR). To determine the clinical presentation, intraoperative and postoperative complications and evaluate the mid-term outcome in VWD patients treated with TAR. Eighteen patients with VWD with mean age 47.3 years (range = 34.0-68.7) were treated for end-stage ankle OA with TAR. The mean duration of follow-up was 7.5 years (range = 2.9-13.2). Intraoperative and perioperative complications were recorded. Component stability was assessed with weight-bearing radiographs. Clinical evaluation included range of motion (ROM) tests using a goniometer and under fluoroscopy using a lateral view. Clinical outcomes were analysed by a visual analogue scale, the American Orthopaedic Foot and Ankle Society hindfoot score and Short Form (36) Health Survey (SF-36) health survey. One patient sustained an intraoperative medial malleolar fracture. In two patients delayed wound healing was observed. Two secondary major surgeries were performed. Pain level decreased from 8.2 ± 0.9 (range = 7-10) preoperatively to 1.1 ± 1.2 (range = 0-4) postoperatively. Significant functional improvement including ROM was observed. All categories of SF-36 score showed significant improvement in quality of life. Mid-term results of TAR in patients with VWD are encouraging. The total rate of intraoperative and postoperative complications was 33.3%. However, longer term outcomes are necessary to fully understand the clinical benefit of TAR in patients with VWD.
Gesehen am 26.11.2018